Letter : Spanish workers' relief - Elvin, Herbert Henry
010-0115-001 NATIONAL UNION of CLERKS & ADMINISTRATIVE WORKERS. TRADE UNION No. 916. APPROVED SOCIETY No. 184. WHEN REPLYING PLEASE QUOTE : Your Ref.: Our Ref.: 80//L/4. Sir Walter Citrine, TRADES UNION CONGRESS GENERAL COUNCIL, Transport House, SMITH SQUARE, S.W.1. Telephone no.: HOLborn 1733 Telegrams: "UNICLERKOS. Phone. London." REGISTERED OFFICE : 17-20, Holborn Hall Gray's Inn Road London. W.C.1. All communications to be addressed to The General Secretary. Write a separate letter for each subject dealt with. 31st August, 1936. Dear Sir Walter, SPANISH WORKERS' RELIEF. I have heard that the Co-operative party has inaugurated a Fund in connection with the struggle of the Spanish Workers in support of the Government. It may be, of course, that this is being done as part of the National Council of Labour appeal, but I thought I would write you about this as it does seem desirable that there should be one Fund only as to avoid overlapping. I have also been informed of monies being sent to the Communist Party of Great Britain. In this instance I was told upon inquiry that all monies received were being sent to the International Solidarity Fund. Yours sincerely, Herbert H. Elvin GENERAL SECRETARY. seen personally HVT. 292/946/10/125